2010
DOI: 10.1159/000258721
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Neuroimmunoendocrine Systems during Post-Traumatic Stress Disorder: A Minireview

Abstract: Early life stress has been suggested to mediate vulnerability to affective disorders. Traumatic events experienced in childhood such as sexual abuse and/or physical neglect may lead to psychiatric diseases in adult life, including post-traumatic stress disorder (PTSD). Previous studies have focused on adult traumatic events and very little is known regarding the long-term physiological effects of early life stress. Here, we review the complex interplay between most important cognitive, neuroendocrine and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 22 publications
(12 reference statements)
2
48
0
1
Order By: Relevance
“…PTSD patients do have activation of innate immune responses and a low-grade systemic proinflammatory state [84] with increased circulating proinflammatory markers [85] and cytokine serum levels positively related to PTSD scores [86]. …”
Section: Ptsd-related Risk Factors For Cardiometabolic Diseasementioning
confidence: 99%
“…PTSD patients do have activation of innate immune responses and a low-grade systemic proinflammatory state [84] with increased circulating proinflammatory markers [85] and cytokine serum levels positively related to PTSD scores [86]. …”
Section: Ptsd-related Risk Factors For Cardiometabolic Diseasementioning
confidence: 99%
“…Skelton et al (2012), Bauer et al (2010), Jovanovic et al (2010), Nowotny et al (2010) having demonstrated that trauma induces neurochemical responses with large time spectrum effect including the magnitude of 7/20 catecholamine and cortisol as Bowirrat et al (2010) exposed, andWu et al (2013) at this subject pointed the interest of the neurobiological systems of resilience research trough comparative studies with trauma exposed individuals whom developed PTSD and those who didn't. Feder, Nestler & Charney (2010) pointed the necessity to study neural circuits that could be underlined resilience aiming the construction of new interventional models, as those illustrated by recent studies based in real-time fMRI, demonstrating the possibility of an individual to perform adequate training and regulate his own brain activity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…experience of a traumatic event) can disrupt the correct function and communication of these two systems [7]. While cytokines are found to be potent stimulators of corticotrophin-releasing hormone and thus activate the HPA axis activity, the HPA axis activation suppresses the activity of cytokines [8].…”
Section: Altered Hpa Axis Function and Impaired Leukocyte Sensitivitymentioning
confidence: 99%
“…The low-grade inflammation phenomenon could also be connected with increased morbidity observed in PTSD [7,27,28]. Evidence linking cardiovascular/autoimmune diseases and exposure to psychological trauma is particularly strong and has been found consistently across different populations and stressor events.…”
Section: Immune Imbalance: Evidence For Low-grade Inflammationmentioning
confidence: 99%